Case report of bouveret syndrome: A strange cause of upper intestinal obstruction (2019)
Bouveret syndrome is a rare pathology which is characterized by gastric or duodenal obstruction secondary to a gallstone embedded in the lumen after migrating through a cholecystoduodenal fistula. Its incidence is approximately 1% to 3% of all cases of biliary ileus. The main symptoms consist of vomiting, abdominal pain, hematemesis, weight loss and anorexia. Surgery is required in 91% of cases. This article presents the case of a 50-year-old patient who had suffered from abdominal pain in the epigastrium and mesogastrium, abdominal distension and multiple episodes of emesis for two months. Physical examination indicated obstruction of the intestine. An abdominal CT scan showed that the obstruction was in the first duodenal portion and that Rigler’s triad was present. It was diagnosed as Bouveret Syndrome. © 2019 Asociaciones Colombianas de Gastroenterología, Endoscopia digestiva, Coloproctología y Hepatología.